Critical Ranges of Zinc in Soils and Leaves in Relation to Visual Symptoms in Apple Orchards of Temperate Jammu and Kashmir, India - Chaudhary, Sanjeev K.; Kotwal, Neeraj; Kumar, Manoj; Sharma, Nirmal; Sharma, Satish Kumar (International Journal of Economic Plants, 2024)
A comparative study of leaf and soil Zn in healthy and unhealthy apple orchards was undertaken to diagnose Zn deficiency in major apple growing blocks of district Doda, Jammu and Kashmir, India during July–August, 2014. Available Zn content in healthy orchards ranged from 1.0–3.6 mg kg-1 in surface soils and from 0.67–2.90 mg kg-1 in sub surface soils of entire district with respective mean values of 1.54 and 1.21 mg kg-1. The corresponding ranges for unhealthy orchards were found to be 0.50–0.99 mg kg-l and 0.40–0.83 mg kg-1 with respective mean values of 0.70 and 0.59 mg kg-1. The overall Zn content in leaves of normal healthy orchards ranged from 24.6–37.5 mg kg-1 whereas in unhealthy orchards, the range was 12.7–28.4 mg kg-1 with respective mean values of 30.36 and 19.25 mg kg-1. Higher Zn status of healthy orchards was ascribed to relatively better management practices being followed in these orchards when compared to others where absentee farming was prevalent. Available Zn showed significant positive correlations with leaf Zn and OC content, both in surface and sub surface soils, whereas its relationship with soil pH was negative. The proposed critical levels of Zn, both in soil and leaf could effectively differentiate the healthy and unhealthy orchards. However, in some cases symptom development could only be attributed to hidden hunger/interactions with other nutrient elements/environment or some external factors.